General conditions for the unique solvability of initial-value problem for nonlinear functional differential equations - Dil'na, N. Z.; Ronto, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish general conditions for the unique solvability of the Cauchy problem for systems of nonlinear functional differential equations.